Evaluation of the Success of the Digital Marketing Implementation of the Reyog Ponorogo Equipment with the Wijayanto Information's System Success Model Approach and Millennial Culture as a Moderating Variable - Heri Wijayanto; Alip Sugianto; Ekapti Wahjuni Djuwitaningsih (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to evaluate the success of the Ponorogo reyog digital marketing system using the Wijayanto Information System success model approach, and the value of millennial culture as a moderating variable. The method used is a quantitative research approach, with a sample of 250 respondents, namely users at start-up reyogku.com and ukmreyog.solution17.com. data analysis using SEM. The results showed that product quality had an effect on use, use had an effect on benefits, and millennial cultural values moderated the quasi, influence of product quality on digital marketing use of Reyog Ponorogo devices. recommendations from the results of this study are the need for digital literacy for reyog Ponorogo craftsmen so that they are able to do marketing through digital marketing, millennial culture in trading products that have historical or cultural values has an important role, so it is necessary to instill cultural values in the millennial generation through digital media.